The research of self preparation of mathematics teacher to apply information technology for the self study of students - Sičiūnienė, Viktorija; Valatkevičienė, Jūratė (Lietuvos matematikos rinkinys, 2013)
How and how often do teachers with more or less experience in this field use Information and Computer Technology (ICT) in their lessons and what are their needs in professional development of this field? In order to answer these questions a research regarding Mathematics teachers’opinion at mainstream schools in April 2013 was carried out. Notices inviting teachers of 4–12th forms to answer on-line questionnaires were sent to schools. By analysing the data received the following conclusions were drawn: the obtained data allows to form a general view about the teachers of Mathematics at mainstream schools, peculiarities of their behaviour that are caused by their personal experience in ICT application for self study of students at various ages. The present article also reveals generalised results of the analysis that was carried out; it presents conclusions and recommendations for educational institutions that organise teacher training and their professional development.
Keywords: ICT usage for mathematics teaching; ICT usage experience